Czy parlament może zmienić mężczyznę w kobietę? Granice i miejsce zasady supremacji parlamentu w brytyjskim porządku konstytucyjnym wobec europejskich procesów integracyjnych (wybrane problemy) - Łukaszewski, Marcin (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
The political system of the United Kingdom of Great Britain and Northern Ireland is of interest to researchers for several reasons. One of the most important motivations certainly involves the unique construction of its Constitution, the content of which is not formulated in a single legal act of a supreme status. This unwritten Constitution encompasses at least four parts. The most important part is undoubtedly constituted by one of three principles of the political system, namely the principle of the sovereignty (omnipotence) of parliament. This principle, which is regarded as a constitutional principle by some and as a principle above the Constitution by others, constitutes the core of British constitutional law. The topic of this paper is an attempt to indicate the boundaries of this principle in the British constitutional order and to place it in relation to remaining principles. The boundaries of this principle have been considered by British constitutionalists on numerous occasions. Considerations on the relation of this principle to the remaining elements of the Constitution have been the subject of interest for courts of law, including the House of Lords, which used to function as the court of last instance in judicial proceedings prior to the 2005 reform. It is worth emphasizing that even the lords/judges frequently disagreed on the boundaries of the principle and even on whether the principle can be examined by any court. There were also views that the principle is only a virtual construct, and even if it had ever applied to the political system at all, it can no longer be referred to, given contemporary European integration processes. The complicated combination of elements of the British constitution with the presence of the United Kingdom in the structures of the European Council and European Union (preceded by the European Community) have produced a number of interpretations of the principle of the omnipotence of the parliament in the new political reality the UK has found itself in. It was the adoption of the European Communities Act 1972, followed several decades later by the adoption of the European Union Act 2011 that led to the discussion on the construction of the British Constitution and either the approval or rejection of the concept that the Constitution of the United Kingdom with its meta-principle should be interpreted anew.
Can a parliament change a man into a woman? The limits and location of the principle of parliamentary supremacy in the British constitutional order in relation to European integration processes (selected issues)
Keywords: zasada suwerenności parlamentu; zasada nadrzędności parlamentu; konstytucja brytyjska; integracja europejska